2022
DOI: 10.1177/10820132221132914
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall composition and enzyme-related activities in eggplant as affected by hot water, 1-MCP and calcium chloride treatments

Abstract: The effects of postharvest applications of hot water (HWT) (45, 50, and 55°C), 1-MCP (1, 5, and 10 μL L−1), and CaCl2 (1, 2, and 3%) on polygalacturonase (PG), pectin methylesterase (PME), α-galactosidase ( α-Gal), β-galactosidase ( β-Gal) and β-1,4-glucanase ( β-1,4-Glu) activities, and the fruit firmness and cell wall composition of eggplant fruit were investigated. The results showed that the decrease in the eggplants firmness was delayed by HWT, 1-MCP, and CaCl2 treatments during storage compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…1 D), indicating that they are involved in softening of grape berries during low-temperature preservation. Calcium and 1-MCP effectively reduced the expression of pectinase and cellulase genes in fruits, thus decreasing their enzymatic activities and the content of soluble pectin and soluble fiber [ 43 , 44 ]. Additionally, Lin (2018) reported that 1-MCP significantly inhibited the activity of cell wall degrading enzymes of Younai plum and reduced the breakdown of cell wall polysaccharides, thus delaying the softening of Younai plum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 D), indicating that they are involved in softening of grape berries during low-temperature preservation. Calcium and 1-MCP effectively reduced the expression of pectinase and cellulase genes in fruits, thus decreasing their enzymatic activities and the content of soluble pectin and soluble fiber [ 43 , 44 ]. Additionally, Lin (2018) reported that 1-MCP significantly inhibited the activity of cell wall degrading enzymes of Younai plum and reduced the breakdown of cell wall polysaccharides, thus delaying the softening of Younai plum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%